Чупа-чуп!: нылпиослы веросъёс / Александр Лаптев - Лаптев Александр Михайлович (Удмуртия, 2013)
Экземпляры: 3 (20160902) / Инвентарный номер: 48975 / Цена: 50.00 / Авт.знак: Л 24 / ГРНТИ: 17.82 / ББК: 84(2Рос.Удм)-5